PENGARUH KELENGKAPAN BERKAS REKAM MEDIS TERHADAP MUTU PELAYANAN KESEHATAN PASIEN RAWAT JALAN DI PUSKESMAS RENSING TAHUN 2022 - Bq. Saadatul Hidayati; Sujarwoko, Sujarwoko (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2022)
This study aims to determine the effect of the completeness of medical record files on the quality of outpatient health services at the Rensing Health Center in 2022. This study used an analytical observational method with a sample of 81 respondents, the statistical test used was Kendall's Tau to determine the effect of completeness of medical record files with quality of outpatient care. The results of this study found the number of incomplete medical record files was 13.6%, incomplete medical record files were found to be 19.7%, and complete medical record files were 66.7%. The quality of service for patients with low quality was found to be 18.5%, quality service was 50.%, and very quality service was 30.9%. The results of the Statistical Test with the Kendall's Tau Test obtained a probability value / p value / Approx Sig = 0.001 < 0.05 (Significant). Because the results are significant, it means that there is an effect of the completeness of the medical record file on the quality of outpatient health services at the Rensing Health Center in 2022.